Application of User-centred Design Method in Laundry Management Application Development - Rizki Pambudi; Gita Fadila Fitriana; Rifki Adhitama (School of Computing, Telkom University, 2021)
On a system from the user side often experience difficulties in its operation. To solve this problem, the laundry management application development process applies the User Centered Design method. The stages taken include Specify the Context of Use and Specify User and Organizational Requirements to identify, determine who the user is and the characteristics of the system user by conducting interviews with laundry business owners. Next, the Produce Design Solution stage is carried out, which is the stage of making a system that can be used by users. The last stage is Evaluate Designs against User Requirements by using Usability Testing to measure the appropriateness and success of the application as well as black box testing to test system functionality. The results of application development and testing using Usability Testing on the aspects of Usefulness, Ease of Use, Ease of Learning and Satisfaction get a feasibility score of 79.8% which means that the development of a laundry management application using the User Centered Design method is feasible because this application is easy to use, easy to learn, provides satisfaction and as expected and is useful for laundry entrepreneurs to manage their transaction data.